2002
DOI: 10.1002/jemt.10197
|View full text |Cite
|
Sign up to set email alerts
|

Cellular distribution of oxygen sensor candidates—Oxidases, cytochromes, K+‐channels—in the carotid body

Abstract: The specific tissue of the carotid body is built up of groups of glomus cells, enveloped by glial-type sustentacular cells, and innervated by sensory nerve fibers. These units sense arterial pO(2) and respond to hypoxia by a variety of reactions that include initiation of the arterial chemoreflex, i.e., increasing firing activity in the carotid sinus nerve. Until now, neither the cellular localization of the initial events that lead to stimulation of chemoreceptor afferents nor the molecular mechanism of oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 54 publications
0
7
0
4
Order By: Relevance
“…The mitochondria of type I cells are different in appearance to those found in both type II cells and sinus nerve endings, with those in the type I cells being the largest with the most cristae and a relatively light matrix (485). Whether these morphological differences are significant for the expression of cell-specific, mitochondrial proteins is not yet known, but mitochondrial function appears closely tied with O 2 sensing and it is apparent that pharmacologically mediated changes in mitochondrial respiration can act like hypoxia to increase Ca 2+ influx and elevate [Ca 2+ ] i (77, 109, 918), induce neurosecretion (748), and cause cell depolarization by inhibition of ca .…”
Section: Sensing Hypoxia—transduction Processes In the Carotid Bodymentioning
confidence: 86%
See 1 more Smart Citation
“…The mitochondria of type I cells are different in appearance to those found in both type II cells and sinus nerve endings, with those in the type I cells being the largest with the most cristae and a relatively light matrix (485). Whether these morphological differences are significant for the expression of cell-specific, mitochondrial proteins is not yet known, but mitochondrial function appears closely tied with O 2 sensing and it is apparent that pharmacologically mediated changes in mitochondrial respiration can act like hypoxia to increase Ca 2+ influx and elevate [Ca 2+ ] i (77, 109, 918), induce neurosecretion (748), and cause cell depolarization by inhibition of ca .…”
Section: Sensing Hypoxia—transduction Processes In the Carotid Bodymentioning
confidence: 86%
“…This K B channel is highly expressed in the type I cell where its properties support the existence of TASK-1-like (112) and TASK-3-like (911) subunit activities that are likely a consequence of a TASK1/3 heterodimer that contributes the principal component of the K B conductance (438, 441). In addition, TASK-2 and TWIK-related arachidonic acid-stimulated K + channel (TRAAK) have also been localized by immunohistochemisty to the type I cell (928) and TASK-1 immunoreactivity has also been reported in the mouse carotid body (423) and human carotid body (261) as well as on rat type II cells (485), although their function on these latter cells has not been determined. The channel has a characteristic, low conductance of ca .…”
Section: Sensing Hypoxia—transduction Processes In the Carotid Bodymentioning
confidence: 99%
“…One of the convincing candidates for the oxygen sensor in carotid body chief cells is the two-pore K + channel, or TASK family (Buckler et al 2000;Kummer and Yamamoto 2002;Yamamoto et al 2002). Hartness et al (2001) reported that the neuroepithelial cell line H146 expressed TASK1 and TASK3, and that hypoxic inhibition of the K + current was abrogated by injection of antisense oligodeoxynucleotides for human TASK1/TASK3.…”
Section: Introductionmentioning
confidence: 99%
“…Andere Arbeitsgruppen konnten zudem zeigen, dass die HPV vom Sauerstoffpartialdruck (PO 2 ) im Blut unabhängig ist und allein durch den PO 2 im Alveolarraum gesteuert wird. Weitere hypothetisch in Frage kommende Sauerstoffsensoren sind Zytochrom P450, das unter Hypoxie oxidiert werden soll (Acker et al, 2006;Fleming et al, 2001;Kummer and Yamamoto, 2002;Porwol et al, 2001;Sylvester and McGowan, 1978), NO-Synthasen, die durch Hypoxie inhibiert werden sollen Dumitrascu et al, 2006;Landmesser et al, 2003;Weissmann et al, 2003b), Mitochondrien (Archer et al, 2006b;Archer et al, 2004;Michelakis et al, 2002;Michelakis et al, 2004;Waypa et al, 2001;Zwicker et al, 1998) phagozytäre und nicht-phagozytäre NADP(H)-Oxidasen (Babior, 2004;Brennan et al, 2003;Ellmark et al, 2005;Liu et al, 2006;Weissmann et al, 2006c).…”
Section: Abbildung 1-6: Schematischer Aufbau Der Gefäßwandunclassified
“…Durch die ROS-Produktion soll das intrazelluläre RedoxPotential verändert und auf diese Weise das Signal weitergeleitet werden, das letztendlich durch Konformationsänderung der K V zur Kontraktion der glatten Muskelzellen unter Hypoxie führt (Gupte and Wolin, 2006;Kummer and Yamamoto, 2002;Lopez-Barneo et al, 2004;Waypa et al, 2001;Weir et al, 2002;Weissmann et al, 2003a;Wolin et al, 2005). Offen hingegen ist die Frage, welche Strukturen zur ROS-Produktion unter Hypoxie beitragen und ob es zu einer vermehrten oder verminderten Freisetzung der Radikale kommt (Aaronson, 2006;Aaronson et al, 2006;Rojas et al, 2006;Sham, 2002;Sylvester, 2001;Weissmann et al, 2006b).…”
Section: Abbildung 1-6: Schematischer Aufbau Der Gefäßwandunclassified